Less is More? Investigating Meta-Learning’s Suitability in Sentence Compression for Low-Resource Data - do R., L. Gustavo Coutinho; de Macêdo, José Antônio F.; da Silva, Ticiana L. Coelho (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2023.233175, 2023)
The sentence compression task is essential in the text summarization process. Unfortunately, the lack of labeled data for specific domains restricts the training of deep learning models to address this problem effectively. In this paper, we present an approach using a meta-learning algorithm called MAML to tackle this issue and assess the viability of this technique for the given task, with particular emphasis on its comparison to a fine-tuned BERT model. Our experiments reveal that a simpler approach involving fine-tuning a language model, such as BERT, might indeed be more effective in low-resource scenarios, consistently outperforming the meta-learning techniques for this particular task.